The Impact of Health Insurance Coverage on Cancer Screening among Women in Thailand - Tangtipongkul, Kaewkwan (Thammasat Review, 2018)
Using data from the 2007 Thai Health and Welfare Survey, this paper analyzes the impact of health insurance coverage and other socioeconomic factors on the likelihood of receiving clinical breast examinations, mammograms, and cervical screening tests among adult women. The paper focuses on breast and cervical screening because breast and cervical cancer are the leading cancer among women in Thailand and early detection increases the likelihood of survival. The author uses logistic regression to produce a cross-sectional estimate of the impact of income and insurance coverage on utilization among Thai women within the past 5 years. The results indicate among low income women the access afforded by the Universal Coverage plan, significantly increases the probability of utilizing cervical screening tests. While among women in the high monthly household income group having the Civil Servant Medical Benefit Scheme and private health insurance increases the propensity to have clinical breast examinations and cervical screening tests. Private health insurance is the only health insurance that has significant and positive probability of having mammograms among women from a high monthly household income group. These results imply that the Universal Coverage plan implemented in 2001 for people without health insurance can assist women in the low monthly household income group to get cervical screening tests with small co-payments.